2020
DOI: 10.3390/ani10101810
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Assessment in Calves Fattened According to the “Outdoor Veal Calf” Concept and in Conventional Veal Fattening Operations in Switzerland

Abstract: The “outdoor veal calf” system was developed to encounter the demand for a veal fattening system that allows for reducing antimicrobial use without impairing animal welfare. Management improvements including direct purchase, short transportation, vaccination, three-week quarantine in individual hutches, and open-air housing in small groups in a roofed, straw-bedded paddock with a group hutch were implemented in a prospective intervention study (1905 calves, 19 intervention and 19 control farms, over one year):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Finally, organic and biologic systems, which are presumed to be welfare-friendly, had lower AMU when compared to conventional systems in many of the studies retained [46,47,49]. This was an expected result.…”
Section: Is the Link Between Animal Welfare And Amu Contributing To T...mentioning
confidence: 73%
See 1 more Smart Citation
“…Finally, organic and biologic systems, which are presumed to be welfare-friendly, had lower AMU when compared to conventional systems in many of the studies retained [46,47,49]. This was an expected result.…”
Section: Is the Link Between Animal Welfare And Amu Contributing To T...mentioning
confidence: 73%
“…Two publications reported a positive effect of welfare-friendly labels on the AMU of fattening calves in Switzerland [47] and in Italy [48]. The former study found that the Swiss "outdoor veal calf" concept had an AMU five times lower when compared to control farms and further investigated whether this reduction was associated or not with "decreased animal welfare, i.e., that sick animals were not left untreated".…”
Section: Publications Debating the Effect Of Animal Welfare On Amumentioning
confidence: 99%
“…Therefore, BCS can be useful as an indirect indicator of health problems such as respiratory disorders. BCS has been used for many years in the management of dairy cows, while it only more recently has been used as a welfare indicator in veal calves (Wilson et al., 2000 ; Renaud et al., 2018 ; Deikun et al., 2020 ; Moser et al., 2020 ; Boyle and Mee, 2021 ); Welfare Quality®, 2009 . BCS was also used in a recent study organised by the New Zealand Government to identify reasons for mortality and morbidity in dairy calves sent for slaughter (so called ‘bobby calves’), and to identify new welfare indicators in these animals (MPI, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Housing type (e.g. igloo vs closed barn), including presence or absence of ventilation Whether the animal is reared indoors or has access to an outdoor run; total air volume and the degree of ventilation can have an impact on the prevalence of respiratory diseases (Moser et al, 2020) Humidity and temperature (temperature humidity index)…”
Section: Sources Of Uncertainty Reasonmentioning
confidence: 99%
“…Data regarding antimicrobial treatments, production parameters, animal welfare and economics were collected during the visits. 3 , 12 , 13 The calves were fattened according to improved welfare standards (IP-SUISSE) alongside milk production in all farms. 14 Farmers worked according to one of two management concepts: the ‘outdoor veal calf’ or ‘conventional’ (19 farms each), as described previously.…”
Section: Methodsmentioning
confidence: 99%